2013
DOI: 10.1542/peds.2012-2362
|View full text |Cite
|
Sign up to set email alerts
|

Misdiagnosed Food Allergy Resulting in Severe Malnutrition in an Infant

Abstract: As food allergies become increasingly prevalent and testing methods to identify "food allergy" increase in number, the importance of careful diagnosis has become even more critical. Misdiagnosis of food allergy and inappropriate use of unproven testing modalities may lead to a harmful food-elimination diet. This case is an example of an infant who was placed on an overly restrictive elimination diet at the recommendation of her health care providers, resulting in kwashiorkor and acquired acrodermatitis enterop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 12 publications
(6 reference statements)
1
6
0
2
Order By: Relevance
“…Prevalence in children is increasing in the developed world 25 . It has recently been reported that children on overly restrictive diets because of suspected food allergy are at risk of deficiency 26 …”
Section: Zn Deficiencymentioning
confidence: 99%
“…Prevalence in children is increasing in the developed world 25 . It has recently been reported that children on overly restrictive diets because of suspected food allergy are at risk of deficiency 26 …”
Section: Zn Deficiencymentioning
confidence: 99%
“…Among the most common food allergens in the pediatric population are milk, wheat and egg (2), which constitute the main sources of significant nutrients, such as protein, iron and calcium (3). An elimination diet creates an emerging need for alternative sources of all basic macro-and micronutrients, as the diet of food allergic children is in several cases found low in energy, protein, calcium, vitamins D and E, iron and zinc (4), due to inappropriate food exclusions and follow-up after diagnosis of food allergies, but also refusal of food allergic children to try new foods (5), resulting to rickets, kwashiorkor, anaemia and failure to thrive in long-term (6). Furthermore, without appropriate dietary education on the everyday management (i.e allergen labelling, alternative foods) (7), psychosocial problems arise (8,9) due to high levels of anxiety associated with a potential accidental reaction (5).…”
Section: Introductionmentioning
confidence: 99%
“…Le danger des tests IgG anti-aliments est qu'ils peuvent être effectués à l'initiative du patient ce qui risque de retarder le diagnostic d'une pathologie pour laquelle il existe une prise en charge thérapeutique efficace [125,127]. Il peut s'agir de MICI, d'allergies alimentaires, de maladies prolifératives, d'une maladie coeliaque.…”
Section: Discussionunclassified
“…Enfin, un régime d'éviction de plusieurs aliments basé sur les résultats d'IgG anti-aliments risque d'entraîner des carences alimentaires ayant des conséquences graves pour la santé, en particulier chez le nourrisson et l'enfant. Aux États-Unis, un nourrisson a été hospitalisé en état de cachexie grave (Kwashiorkor et acrodermatite enteropatica) car ses parents avaient mis en place un régime d'éviction des aliments positifs en IgG sur le conseil d'un naturopathe [127].…”
Section: Discussionunclassified